Towards Developing Novel Prostate Cancer Recurrence Suppressors: Acute Toxicity of Pseurotin A, an Orally Active PCSK9 Axis-Targeting Small-Molecule in Swiss Albino Mice - Oliver C. McGehee; Hassan Y. Ebrahim; Ashkan H. Rad; Khaldoun S. Abdelwahed; Ethar A. Mudhish; Judy A. King; Iman E. Helal; Sharon A. Meyer; Khalid A. El Sayed (Molecules, 2023)
The proprotein convertase subtilisin kexin type 9 (PCSK9) emerged as a molecular target of great interest for the management of cardiovascular disorders due to its ability to reduce low density lipoprotein (LDL) cholesterol by binding and targeting at LDLR for lysosomal degradation in cells. Preliminary studies revealed that pseurotin A (PsA), a spiro-heterocyclic γ-lactam alkaloid from several marine and terrestrial Aspergillus and Penicillium species, has the ability to dually suppress the PCSK9 expression and protein–protein interaction (PPI) with LDLR, resulting in an anti-hypercholesterolemic effect and modulating the oncogenic role of PCSK9 axis in breast and prostate cancers progression and recurrence. Thus, a preliminary assessment of the PsA acute toxicity represents the steppingstone to develop PsA as a novel orally active PCSK9 axis modulating cancer recurrence inhibitor. PsA studies for in vitro toxicity on RWPE-1 and CCD 841 CoN human non-tumorigenic prostate and colon cells, respectively, indicated a cellular death shown at a 10-fold level of its reported anticancer activity. Moreover, a Western blot analysis revealed a significant downregulation of the pro-survival marker Bcl-2, along with the upregulation of the proapoptotic Bax and caspases 3/7, suggesting PsA-mediated induction of cell apoptosis at very high concentrations. The Up-and-Down methodology determined the PsA LD50 value of >550 mg/kg in male and female Swiss albino mice. Animals were orally administered single doses of PsA at 10, 250, and 500 mg/kg by oral gavage versus vehicle control. Mice were observed daily for 14 days with special care over the first 24 h after dosing to monitor any abnormalities in their behavioral, neuromuscular, and autonomic responses. After 14 days, the mice were euthanized, and their body and organ weights were recorded and collected. Mice plasma samples were subjected to comprehensive hematological and biochemical analyses. Collected mouse organs were histopathologically examined. No morbidity was detected following the PsA oral dosing. The 500 mg/kg female dosing group showed a 45% decrease in the body weight after 14 days but displayed no other signs of toxicity. The 250 mg/kg female dosing group had significantly increased serum levels of liver transaminases AST and ALT versus vehicle control. Moreover, a modest upregulation of apoptotic markers was observed in liver tissues of both animal sexes at 500 mg/kg dose level. However, a histopathological examination revealed no damage to the liver, kidneys, heart, brain, or lungs. While these findings suggest a possible sex-related toxicity at higher doses, the lack of histopathological injury implies that single oral doses of PsA, up to 50-fold the therapeutic dose, do not cause acute organ toxicity in mice though further studies are warranted.